Specification for control switches (switching devices, including contactor relays, for control and auxiliary circuits, for voltages up to and including 1000 V a.c. and 1200 V d.c.). Contactor relays. Pilot switches Part 2 Sections 2.3 and 2.4, (31st October 1977) - British Standards Institution,
No abstract available